Ascariasis, trichuriasis and fatal non-transfusion - Larry Nichols; Joshua Curtis Bridgewater; Nicholas Brennan Wagner (University of São Paulo, 2021)
Blood transfusion for chronic anemia can lead to acute or decompensated heart failure in patients who have fluid overload as part of their compensatory response and/or have intrinsic heart disease, and then it could be fatal in such clinical scenarios. This is the report of a case of profound chronic anemia in a young male patient, who was not transfused and then developed confusion followed by terminal cardiopulmonary arrest. Autopsy revealed severe trichuriasis to be the cause of the anemia, along with severe ascariasis, but minimal intrinsic brain disease. This supports the conclusion that anemia was the cause of the confusion, and the lesson that confusion may be a sign that the benefit of blood transfusion outweighs the risk in a patient with severe chronic anemia.